Efforts to Increase Students' Learning Achievement On Fraction Materials in Class V Semester 1 Through The Application Of The Make a Match Learning Model In Sd Negeri Dawuhan 03 Academic Year 2019/2020 - Aryanti, Novi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The research objective to be achieved is to improve student learning achievement in fractional material in class V SD Negeri Dawuhan 03, Sirampog District, Brebes Regency for the 2019/2020 academic year through the Make a match learning model. This form of research uses Classroom Action Research. The research subjects used were the fifth grade students of Dawuhan 03 State Elementary School, Sirampog District, Brebes Regency for the 2019/2020 academic year as many as 37 students. The results of the study can be seen that the percentage of student learning completeness in cycle 1 of 37 students there are 26 (81.08%) students who complete and the rest 11 (29.72%) students have not obtained completeness, with an average value of 79 ,02. In cycle 2 of 37 students there were 35 (94.59%) students who completed and the remaining 2 (5.40%) students had not obtained completeness with an average value of 90.32. Based on the available information, it can be concluded that the use of the make a match learning model can improve student learning achievement on fraction material in class V SD Negeri Dawuhan 03.